Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1128/jb.182.2.400-404.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Multiple Drug Resistance Gene MDR1 in Fluconazole-Resistant, Clinical Candida albicans Strains Is Caused by Mutations in a trans -Regulatory Factor

Abstract: Resistance of Candida albicans against the widely used antifungal agent fluconazole is often due to active drug efflux from the cells. In many fluconazole-resistant C. albicans isolates the reduced intracellular drug accumulation correlates with constitutive strong expression of the MDR1 gene, encoding a membrane transport protein of the major facilitator superfamily that is not detectably expressed in vitro in fluconazole-susceptible isolates. To elucidate the molecular changes responsible for MDR1 activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 30 publications
2
72
0
2
Order By: Relevance
“…Wirsching et al demonstrated that in two independent FLC R clinical strains of C. albicans, MDR1 overexpression was due to mutations in an unidentified trans-regulatory factor(s) (54). We have demonstrated that in five independently isolated FLC R laboratory strains, MDR1 overexpression was also achieved through trans-activation of MDR1, suggesting that this may be the most common mechanism for MDR1 overexpression.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Wirsching et al demonstrated that in two independent FLC R clinical strains of C. albicans, MDR1 overexpression was due to mutations in an unidentified trans-regulatory factor(s) (54). We have demonstrated that in five independently isolated FLC R laboratory strains, MDR1 overexpression was also achieved through trans-activation of MDR1, suggesting that this may be the most common mechanism for MDR1 overexpression.…”
Section: Discussionmentioning
confidence: 73%
“…In some FLC R strains, high-level expression of MDR1 is due to the effects of an undefined trans-acting factor(s) (54). Recent work by Hiller et al indicates that three independent regions of the MDR1 promoter are capable of contributing to MDR1 expression in a FLC R strain overexpressing MDR1 and that the portion of the MDR1 promoter they term region 2 (Ϫ588 to Ϫ500) mediates benomyl induction of MDR1 transcription in the FLC-sensitive (FLC S ) laboratory strain CAI4 (29).…”
mentioning
confidence: 99%
“…In our experimental populations, CAP1 was not significantly altered in expression and no mutations were detected in the DNA sequence (data not shown). In both yeasts, the interactions in the transcriptional networks regulating multidrug transporters have yet to be experimentally dissected (27,29). In addition to transcriptional coregulation, adaptive mutations could have indirect pleiotropic effects (30) on the expression of suites of genes through interactions among various gene products (8), signaling activity across different pathways (31), or changes in cell physiology (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, a dramatic transient upregulation of MDR1 can be observed in azole-susceptible strains after treatment with toxic hydrophobic agents (benomyl, methotrexate, 4-NQO, o-phenanthroline), oxidizing agents [diamide, H 2 O 2 , tert-butyl hydrogen peroxide (T-BHP) and diethylmaleate] and the alkylating agent methyl methanesulfonate (Gupta et al, 1998;Harry et al, 2005). Clinical isolates with increased MDR1 expression have not undergone amplification of the MDR1 gene (Wirsching et al, 2000a). Sequence analysis of MDR1 promoters from clinical isolates compared to wild-type promoters did not reveal cis-acting mutations (Harry et al, 2005;Wirsching et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%